Age features of O2 mass transfer regimes in adolescents' body at rest - D. Komolafe; M. Filippov; V. Ilyin; A. Klimenko (Kazimierz Wielki University, 2021)
The results of complex studies of the quantitative relationship between the stage-by-stage mass transfer of O2 and the efficiency of cardiorespiratory system functioning in relation to its consumption in adolescents' body under conditions of relative rest are presented. The results obtained show that in adolescents, the modes of mass transfer of O2 in the body and the nature of the respiratory and circulatory systems functioning in relation to its consumption have a number of age-related differences compared with adult men. So, in adolescents, the external respiration system at rest functions less economically than in adults. Each liter of O2 consumed by adolescents is extracted from almost 3 liters more than in adults the amount of air ventilated per minute through the lungs. The volumetric indicators of blood circulation are also higher in adolescents, which may indicate the influence of neuro-humoral rearrangements in the body during the pubertal period. The coefficient of oxygen utilization by tissues from arterial blood in adolescents turned out to be significantly higher, which may characterize a higher tension of tissue metabolic processes.